Artistic Interpretation Of ReligiousMythological Motives In GrecoRoman Literature - Muxtorova Umida Tolib kizi (Genius Journals, 2023)
This article explored the artistic synthesis of motifs and narratives in world and national literature. Samples of the plays of Chingiz Aitmatov were compared with analytical comparative evidence with Western sources. In addition, scientifically based the directions in Uzbek and world literature related to divine-religious motives, methods of using mythology.
Keywords: artistic synthesis; mythological observation; conception